Lumber drying of pinus: Geostatistics applied to drying kilns - Schaeffer, Winicius Augusto; Campos Monteiro, Thiago; Klitzke, Ricardo Jorge; Pelissari, Allan Libanio; Francisco Juizo, Claudio Gumane; da Silva Lins, Tarcila Rosa (Maderas. Ciencia y Tecnología, 2022)
This study aimed to evaluate the spatial distribution of the air circulation speed and the final moisture content of pine lumber after kiln drying by using geostatistics. Two kilns acting on boards of 27 mm and 42 mm were evaluated. Air circulation speed and final moisture content were collected in different regions of the kilns. There was no significant difference for air circulation speed and final moisture content between the front and rear regions of the equipment. In the horizontal axis (Y-axis), air circulation speed averages did not differ statistically in both situations, but higher values ​​for this variable were obtained from the spaces between the piles. Final moisture content tended to increase when closer to the door opening. In the vertical axis (Z-axis), the lower part tended to reach higher air circulation speed values. Thus, the spatial behavior influences the air circulation speed and final moisture content during lumber drying. Besides, the variograms presented the same tendency in comparison to the data obtained in a conventional manner, which indicates that geostatistics can be used to represent variables in kilns during the drying process.